Family and general educational institution - Vakelishvili, Nino; Kakalashvili, Zeinabi (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The article presents the role of the family in a general educational institution, in child rearing and education. Family and the general educational institution - school - are two necessary spheres for the socialization of the child. Their educational functions are different, but for the full development of the child, it is necessary that they work together. At school, a child receives education, learns to communicate with other children, coordinate their actions, and more, but how effectively all this is implemented depends on the relationship between the family and the school. It is impossible not to properly assess the great importance of the role of the family in raising a child. Family plays the most important role in a child's life. On their development, establishment of a place in society, formation of personal values, and mental health. It is important that the cooperation between the family and the school plays an important role in the development and continuity of the child, it is necessary to know the opinions of teachers and parents about each other. Recommendations need to be developed to help these two institutions interact effectively. For this, we need to know the history, how these relations developed. The article describes some research-based preventive tasks for the psychological-pedagogical education of parents, which were carried out in several schools in Telavi. It is also described how to solve them purposefully and comprehensively. Mutual cooperation between family and school guarantees the development of the child's personal qualities. We believe that such cooperation will significantly increase the number of successful students, increase the quality of communication between parents and teachers, which will help them act only in the best interest of the child. All this has a positive impact on the image of the school in society and the community.